Oxford handbook of clinical medicine - Wilkinson, Ian; Raine, Tim; Wiles, Kate; Hateley, Peter; Kelly, Dearbhla; McGurgan, Iain (New York : Oxford University Press, 2024)
"I swear by Apollo the physician and Asclepius and Hygieia and Panacea and all the gods and goddesses, making them my witnesses, that I will fulfil according to my ability and judgement this oath and this covenant. To hold him who has taught me this art as equal to my parents and to live my life in partnership with him, and if he is in need of money to give him a share of mine, and to regard his offspring as equal to my own brethren and to teach them this art, if they desire to learn it, with-out fee and covenant. I will impart it by precept, by lecture and by all other manner of teaching, not only to my own sons but also to the sons of him who has taught me, and to disciples bound by covenant and oath according to the law of physicians, but to none other. The regimen I shall adopt shall be to the benefit of the patients to the best of my power and judgement, not for their injury or any wrongful purpose. I will not give a deadly drug to anyone though it be asked of me, nor will I lead the way in such counsel.1 And likewise I will not give a woman a pessary to procure abortion.2 But I will keep my life and my art in purity and holiness. I will not use the knife,3 not even, verily, on sufferers of stone but I will give place to such as are craftsmen therein. Whatsoever house I enter, I will enter for the benefit of the sick, re-fraining from all voluntary wrongdoing and corruption, especially se-duction of male or female, bond or free"--
1.Thinking about medicine -- 2.History and examination -- 3.Cardiovascular medicine -- 4.Chest medicine -- 5.Endocrinology -- 6.Gastroenterology -- 7.Kidney medicine -- 8.Haematology -- 9.Infectious diseases -- 10.Neurology -- 11.Oncology and palliative care -- 12.Rheumatology -- 13.Surgery -- 14.Clinical chemistry -- 15.Eponymous syndromes -- 16.Radiology -- 17.Reference intervals, etc. -- 18.Practical procedures -- 19.Emergencies